Factors Influencing SME Performance of Incubation Beneficiaries in South Africa - Mweli, Sibusisiwe (University of the Witwatersrand, Johannesburg, 2024)
The focus of the research study was to investigate the factors that have contributed to the performance of the SMEs after incubation, with a focus on their dynamic capabilities, innovation capabilities, and the role of incubator support. A descriptive, quantitative study was conducted, employing a structured questionnaire as the data collection tool to capture the factors impacting SME performance post-incubation. The study included 43 SMEs, identified from incubator organizations across South Africa, LinkedIn, and various entrepreneur WhatsApp groups, who had successfully completed an incubation program. The findings of the study revealed that SME dynamic capabilities and innovation significantly predict SME performance post-incubation. However, the study's results also showed that incubator support does not moderate the relationship between innovation and SME performance, implying that current incubator support efforts do not significantly influence SME performance after incubation. The study recommends that to maximize their influence on SMEs' performance after incubation, incubators should put in place programs that assist the growth of SME dynamic capabilities and creative ideas. It also emphasizes how important it is to learn more about the difficulties and obstacles preventing SMEs from performing well both during and after incubation. To validate these results, more research with larger samples is required because of the small sample size. In the future, researchers should also investigate the specific ways that small businesses' changing abilities affect their performance, as well as the outside factors that affect how well incubator support works for small business performance.
A research report submitted in partial fulfillment of the requirements for the degree of Master of business administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: SME Performance; Incubation; Dynamic Capabilities; Innovation; UCTD; SDG-8: Decent work and economic growth